Nusyus Pada Khi Perspektif Gender Dan Maqosid Syariah Jasser Auda - Fitrotin Jamilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Some contemporary Islamic religionists argue that the concept of nusyuz in Article 84 of the compilation of Islamic law (KHI) is discriminatory against women. In that clause, many obligations are delegated to women. If the wife cannot perform her obligations, then the nusyuz law applies, but not to the husband. In this context there is ambivalence, ambiguity and legal injustice. Therefore, this paper discusses the meaning of nusyuz in KHI from a gender perspective and its relevance in the development of Islamic law in Indonesia. This literature research with historical approach and gender analysis shows: first, the relevance of the concept of nusyuz in fiqh and KHI lies in its ruling implicit implications of understanding the substance of textuality; second, the redefinition of the nusyuz concept through Jasser Auda's maqashid al-syariah system approach to protect and develop women's human rights is to complement the concept of nusyuz husbands in Article 84 KHI. Thus, the principle of equality and justice is an important aspect in the reinterpretation of the concept of nusyuz, which can be carried out by both the wife and the husband.